Immediate and Medium-Term (6 Months) Results of BVS Absorb Biodegradable Coronary Scaffolds Installation in Patients with Chronic Forms of Coronary Artery Disease - V. V. Fomenko; D. G. Ioseliani; D. A. Asadov; S. P. Semitko (Неотложная медицинская помощь)
Aim of study To evaluate the immediate and medium-term (6 months) results of BVS Absorb biodegradable stents implantation in patients with chronic forms of coronary artery disease, taking into account their location in coronary vessels, morphological nature of the initial lesion of the coronary arteries and technical features of implantation as well.Material and methods From June 2014 to December 2015, 199 biodegradable stents (Absorb Bioresorbable Vascular Scaffold — BVS; Abbott Vascular, CA, USA) were routinely installed in 114 patients treated at the Interventional Cardioangiology Center of I.M. Sechenov First Moscow State Medical University. The analysis of the obtained results was carried out depending on the type of coronary artery lesion, the length and diameter of the stents, and the details of the angioplasty procedure. To characterize the type of coronary artery lesion, the ACC/AHA classification was used: type A vascular lesion (95 coronary segments); type B vascular disease (68 coronary segments); type C vascular disease (36 coronary segments). The ultimate goal of the study was to study the frequency of thrombosis and in-stent stenosis of stented coronary arteries.Results The immediate success of scaffold implantation was 98.2%. Complications in the early hospital period were 1.8% (acute stent thrombosis was observed in 2 cases on the first day after implantation). In the medium-term (~6 months), 102 patients (89.5%) with 172 previously placed stents underwent comparison selective coronary angiography. The rest of the patients with stents refused to undergo coronary angiography due to good health and underwent a telephone survey.The satisfactory result of stenting in the medium-term (6 months) was a completely preserved lumen of the stented area, or with less than 50% stenosis of this place, which comprised 94.3%. The frequency of in-stent stenosis (narrowing of the lumen of the stented area by 50% or more) was 5.7%. In-stent stenosis was detected in groups of patients with type B and C lesions, respectively, in 4% and 1.7%. In the group with type A coronary artery disease, in-stent stenosis was not detected in the medium-term period.Conclusion The immediate and medium-term results of stenting with the biodegradable BVS Absorb stent were successful in the vast majority of cases (94.3%). Only in 2 cases (1.8%), acute thrombosis of the stent was observed immediately after stenting.